Resiliencia como estrategia de afrontamiento en pacientes con insuficiencia renal crónica que se realizan hemodiálisis en Dial-Ríos, Vinces - Aguirre Alarcón, María Yuliana (2017)
The present study aimed to determine how resilience influences as a coping strategy in patients with chronic renal failure who undergo hemodialysis in Dial-Ríos, Vinces. In order to carry out this work, a previous investigation was made of the patients' situation, in relation to their treatment, frequency of the same, everything that entails the same (diet, care, etc) and collaboration of the patients to maintain stable their state Health. To carry out the research, a group of 118 patients was taken as a sample for the application of the instruments, these were: the questionnaire of perception of the disease and a survey, the results were interpreted by means of the analysis of each question both of the questionnaire and of The survey and then established the respective conclusions and recommendations. Once the analysis of the study was carried out, it was concluded that the resilience positively influences the patients and helps them to have a better perception of their situation, then a proposal was elaborated as a result of the investigated, to solve the problem raised in Research and collaborate with the improvement of the quality of life of the patient.